Karl Sax's Letters about "the Bosnian Turks" and the Turkish language in Bosnia (19th c.) - Čaušević, Ekrem (Array, 2012)
In the second half of the 19th century, Bosnia and Herzegovina was more frequently visited by foreign diplomats and travellers from European countries. Upon their return to their countries, some of these visitors would publish a variety of texts (mainly travelogues) about their travel experiences in this westernmost province of the Ottoman Empire. These travelogues frequently mention the facts related to the geographical characteristics of Bosnia and Herzegovina, its natural abundance and beauty, its cities, roads, economy, government, inhabitants, lifestyle, customs, attitudes of Muslims towards non-Muslim population, freedom of religion, and other liberties. A Turkologist with an interest in linguistic and cultural aspects of that period, however, can find very little information of interest in these sources other than the few statements that "very few Bosnians (of all denominations) speak Turkish" , that "even those who speak Turkish can barely communicate in this language" and that "the local Turks (the Bosnian Muslims) speak the native (Slavic) language with each other". The two authors in this period that do focus on the languages and culture of Bosnian Muslims in their publications are the Prussian Consul Otto Blau in Bosnisch-türkische Sprachdenkmäler, and Carl Sax, a senior official at the Austrian Consulate in Sarajevo. In 1862 and 1863, Carl Sax published two letters that he had originally sent to a German professor called Wickerhauser. The letters were published in a German periodical titled the Zeitschrift der Deutschen Morgenländischen Gesellschaft. The letters from Professor Wickerhauser to Carl Sax were not preserved, but from Sax´s replies to Professor Wickerhauser, it is evident that Carl Sax was asked to provide detailed information about the Turkish language in Bosnia, about “the Bosnian Turks” (i.e. Bosnian Muslims), and how much knowledge they had about the Turkish literature and its literary classics. Although Sax´s information and judgements about the Bosnian Muslims and their knowledge of the Turkish language and literature can not be taken without some reservation, his letters, nevertheless, provide important information about the Bosnian variety of the Turkish language. This paper is dedicated to Sax's letters, which have so far not been available to Turkologist.